Determining time resolution of microchannel plate detectors for electron time-of-flight spectrometers - Zhang, Qi (张琦); Zhao, Kun (赵昆); Chang, Zenghu (常增虎) (My University, 2010)
The temporal resolution of a 40 mm diameter chevron microchannel plate (MCP) detector followed by a constant fraction discriminator and a time-to-digital converter was determined by using the third order harmonic of 25 fs Ti:sapphire laser pulses. The resolution was found to deteriorate from 200 to 300 ps as the total voltage applied on the two MCPs increased from 1600 to 2000 V. This was likely due to a partial saturation of the MCP and/or the constant fraction discriminator working with signals beyond its optimum range of pulse width and shape.